A Study of the inhibitory effect of Terpinen-4-ol on Amastigote Forms of Leishmania tropica within Macrophages of Mouse in vitro - Hami, Abdulazim Mohammed (Iraqi Journal of Pharmaceutical Sciences, 2022)
It was recorded that Terpinen-4-ol has an anti-parasitic properties, so it will be noteworthy to intensify the studies about this compound. This study aims to test the effectiveness of terpinen-4-ol on amastigote forms of Leishmania parasite in macrophages. This effect was studied by adding increasing concentrations of Terpinen-4-ol to culture wells containing mouse macrophages that were previously incubated with the promastigote forms of the parasites for 24 hours .Then, they were incubated for another 24 hours with increasing concentrations of Terpinen-4-ol. After, Parasites were enumerated into macrophages in wells either treated with Terpinen-4-ol or in control wells. Treatment with Terpinen-4-ol at concentrations (0.01%, 0.02%, 0.05%, 0.1%) (v/v) decreased the viability of the amastigote forms inside macrophages (24.02%, 32.74%, 66.72%, 100%) respectively, compared to control wells (water only). This study demonstrated an activity of Terpinen-4-ol against amastigote forms of Leishmania tropica in vitro with minimal inhibitory concentration (MIC50) value was 0.0416% (v/v).